Laporan Kasus : Kematian Mendadak Seorang Pria Berusia 51 Tahun Case Report: Sudden Death of a 51-Year-Old Man - Azizah, Nada Nur; Adhayati , Baety; Kaurow , Farah Primadani (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Sudden death is defined as a natural death that occurs suddenly, unexpectedly, is witnessed, and occurs within 1 hour after the onset of symptoms or, if not witnessed, within 24 hours after the last seen alive and symptom-free. One hospital in Ethiopia reported that 4,942 autopsies were performed in 2020-2021, with 568 cases caused by sudden death. The primary cause of sudden death is cardiovascular disease. Additionally, more than one-third of the cases had a history of chronic illness, with diabetes mellitus being the most common condition. This report includes an analysis of the case of a 51-year-old man who was referred to the Cilegon City Social Service Department with a diagnosis of post-excisional debridement ulcer disease and a history of diabetes mellitus. The following day, the victim was found lying down, suspected to have passed away in his room.